Ambivalence in the Early Years of Marriage: Impact on Ambulatory Blood Pressure and Relationship Processes. Issue 12 (22nd April 2019) - Birmingham, Wendy C; Wadsworth, Lori L; Hung, Man; Li, Wei; Herr, Raphael M
Abstract : Individuals in early marriage who reported spousal ambivalent behavior exhibited higher blood pressure and worse relationship processes. This was supported by both subjective and objective measures. Abstract: Background: Marriage is associated with lower cardiovascular morbidity and mortality, but quality matters. Marriages characterized by ambivalent behaviors (containing both highly positive and highly negative behaviors concurrently) may not confer the same cardiovascular benefits as characterized by purely positive behavior. Ambivalence is assumed to take time to develop but couples in the early years of marriage may already exhibit ambivalent behaviors and thus be at increased risk for future cardiovascular events. Purpose: The purpose of this study was to determine the frequency of spouse and own ambivalent behavior, the impact on interpersonal (i.e., responsiveness, disclosure, affective interactions) processes, and ambulatory blood pressure (ABP) in individuals in the early years of marriage. Methods: In 84 young married couples, objective and subjective ambivalence, interpersonal functioning, and ABP over a 24-hr period were assessed. Results: As predicted, ambivalence developed early in marriage. Regarding interpersonal processes, spousal and own objective ambivalent behavior was associated with lower spousal responsiveness ( p < .01), disclosure ( p < .05), and more negative ( p < .03) and less positive interactions ( p < .001). Physiologically, ambivalent spousal behavior was associated with higher systolic blood pressure ( p = .02) and higher diastolic blood pressure ( p = .04). Measures of subjective ambivalence were congruent. Conclusions: Early marriages already contain ambivalent behavior; in such cases, individuals may not receive the cardiovascular protection of a supportive marriage.